MODEL BANGKITAN PERGERAKAN ZONA KECAMATAN PALU BARAT KOTA PALU - Ismadarni, Ismadarni (MEKTEK, 2010)
The trip generation is a submodel of four steps transportation planning model, used for calculating the mount of trip generation caused by land usage. The aim of this research is modeling the trip generation of Western Palu Region used by regression analyses. Data of traveler characteristics in study area i.e, amount of daily movement, number of family members,number of car ownerships, the amount of income were collected with a survey used quisioner methods.The result of this research found that the model of trip generation of Western Palu Region followed the multiple regression model, Y= 0,679+ 0,608X1 + 0,274X2 with coefficient of determination value, R2=0,294